1997
DOI: 10.1111/j.1744-7917.1997.tb00109.x
|View full text |Cite
|
Sign up to set email alerts
|

SEX PHEROMONE COMPONENTS OF HELICOVERPA ARMIGERA:CHEMICAL ANALYSIS AND FIELD TESTS*

Abstract: Gas chromatographic and mass spectral analyses were conducted on the pheromone gland extracts of female moth of Helicoverpa armigera (Lepidoptera:Noctuidae). Saturated aldehyde (16:Ald), (Z)‐9‐hexadecenal (Z‐9–16:Ald), (Z)‐11‐hexadecenal (Z‐11–16:Ald), hexade‐canol (16:OH) and (Z)‐11‐hexadecenol (2–11–16:OH) were found from gland extracts in the ratio of 6.1:4.5:100:3.5:8.8. In field tests of Shandong and Shanxi Provinces, 2 mg blends of Z ‐11–16:Ald and Z‐9–16:Ald (97:3) applied on a rubber dispenser effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…H. armigera and H. assulta are sympatric, closely related species in and around China. In H. armigera, the ratio of the major pheromone component, Z11-16:Ald and the minor component, Z9-16:Ald varied from 100:6.5 to 100:2.5 (Nesbitt et al, 1980;Wu et al, 1997;Dunkelblum et al, 1980;Kehat and Dunkelblum, 1990). The variation could have been caused by collection of experimental insects from different areas.…”
Section: Introductionmentioning
confidence: 90%
“…H. armigera and H. assulta are sympatric, closely related species in and around China. In H. armigera, the ratio of the major pheromone component, Z11-16:Ald and the minor component, Z9-16:Ald varied from 100:6.5 to 100:2.5 (Nesbitt et al, 1980;Wu et al, 1997;Dunkelblum et al, 1980;Kehat and Dunkelblum, 1990). The variation could have been caused by collection of experimental insects from different areas.…”
Section: Introductionmentioning
confidence: 90%
“…For H. armigera, more than seven pheromone components have been identified from the pheromone glands of females. 14,161,162 When the pheromone components Z11-16: Ald and Z9-16:Ald are mixed at a ratio of 99:1 as compared to 90:10, attractiveness to the males is significantly increased. 161,163 Z9-14:Ald was shown to strengthen the attraction of males at low concentrations, while suppressing attraction at higher concentrations, when mixed with the pheromone components.…”
Section: Behaviormentioning
confidence: 97%
“…8,9 The variation of the double bond position and the differentiation of the pheromone component proportions may underlie reproductive isolation barriers between species. 4,[10][11][12][13][14] This is exemplified by the two sex pheromone races of the European corn borer moth Ostrinia nubilalis, E and Z, which produce opposite ratios of isomers of the major female sex pheromone components, E11-and Z11-14:acetate. 15, 16 Lassance et al found that allelic variation in a fatty-acyl reductase gene that is essential for pheromone biosynthesis accounts for the female pheromone variation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important sex pheromone component for the species is (Z)-11-hexadecenal (Z11-16:Ald), which alone can attract a small number of male moths. Z9-16:Ald is generally thought to be an important minor component [25], [26], [27], [28], [29]. Adding Z9-16:Ald to Z11-16:Ald with ratio from 1∶99 to 10∶90 caused a significant increase in trap catch of male H. armigera [27], [30], [31].…”
Section: Introductionmentioning
confidence: 99%
“…Adding Z9-16:Ald to Z11-16:Ald with ratio from 1∶99 to 10∶90 caused a significant increase in trap catch of male H. armigera [27], [30], [31]. Many other components were also identified in sex pheromone glands of female H. armigera , including tetradecanal (14:Ald), (Z)-11-tetradecenol (Z11-14:OH), (Z)-9-tetradecanal (Z9-14:Ald), 16:Ald, Z7-16:Ald, 16:OH, Z9-16:OH, Z11-16:OH, Z11-14:Ald and Z11-16:Ac [27], [29], [32], [33]. Of these, Z11-16:OH and 16:OH are attraction inhibitors when added to attraction blends [27], [29], [30].…”
Section: Introductionmentioning
confidence: 99%